Supermarket differentiation in the UK : a theoretical and empirical investigation. - Obitz, Cornelia (Diplomica Verlag, 2009)
This book examines and explains the current situation and problems of supermarket chains in England. Supermarket chains are operating in a profitable market but they are confronted with the problem of high competition and compared to manufacturers they have only few possibilities to differentiate. Especially the importance of differentiation is questioned in this book. It is examined whether differentiation is really essential for gaining competitive advantage. For a comprehensive and substantiated demonstration secondary theoreatical data and a study with primary data is used. With theories of.